Correlation between hsCRP and Anti-beta2GPI Antibody in Metabolic Syndrome - Meiriza Djohari; Mansyur Arif; Burhanuddin Bahar (The Prodia Education and Research Institute (PERI), 2011)
BACKGROUND: Several researches reported that inflammatory and immunological mechanism such as autoantibody to β2-glycoprotein I (anti β2GPI) appear as related factors in initiation and progress of atherosclerosis lesion in patient with autoimmune disease. Antibody to β2GPI titers are correlated with atherosclerosis and in vitro studies showed that they enhance oxidized low density lipoprotein (ox-LDL) uptake by macrophages. Immunization with auto-antigen β2GPI elicits an immune response to influence lesion progression that mostly happens in autoimmune subjects. The metabolic syndrome (MetS) is combination of several metabolic disorders such as obesity, dyslipidemia, Diabetes Mellitus (DM) and conditions due to inflammation and stress oxidative. The Correlation between inflammatory markers such as High sensitivity C-Reactive Protein (hsCRP) and anti-β2GPI antibody in MetS needs to be further investigated.METHODS: This was an observational study with cross sectional design on subject with MetS as determined by the International Diabetes Federation (IDF) 2005’s criteria.RESULTS:There was a positive and significant correlation between hsCRP and anti-β2GPI antibody in MetS group (r=0.406; p≤0.05) as compared to non-MetS group. We found that there was elevated level of anti-β2GPI antibody in hsCRP of 3-10 mg/L.CONCLUSIONS: Anti-β2GPI antibody may be elevated in subjects with MetS who have low grade of inflammation as shown by hsCRP.KEYWORDS: metabolic syndrome, inflammation, autoantigen, atherosclerosis, obesity